Evidence on the prevalence, incidence, mortality and trends of human papilloma virus-associated cancers in sub-Saharan Africa: systematic scoping review - Kabelo M. B. Lekoane; Desmond Kuupiel; Tivani P. Mashamba-Thompson; Themba G. Ginindza (BMC Cancer, 2019)
Abstract Background Human papilloma virus (HPV) associated cervical cancer remains a global concern particular, in Sub-Saharan Africa (SSA) where the impact is felt most. Evidence show that many other cancers such as vaginal, anal, oropharyngeal, penile are because of persistent infection with HPV especially, high-risk types. Aim We mapped evidence on the incidence, prevalence, mortality, and the trends of human papillomavirus-related cancers in SSA. Methods A comprehensive literature search was conducted from several databases including PubMed, Google scholar, Science Direct, and CINAHL and MEDLINE via EBSCOhost as well as World Health Organization website for grey literature. Studies reporting HPV-related cancers in SSA outcomes including prevalence, incidence, mortality, and trends were included in this study. The risk of bias of the included studies were assessed using the mixed methods appraisal tool version 2011. We employed PRISMA (preferred reporting items for systematic reviews and meta-analyses) to report the search results. Thematic analysis used to reveal the emerging themes from the included studies. Results Seventy-four (74) studies were retrieved at full article screening, eight of them (six reviews, and two quantitative study) were eligible for data extraction. The degree of agreement between the two independent reviewers following full article screening, was 86.49% agreement versus 64.57% likely by chance which constituted moderate to significant agreement (Kappa statistic = 0.62, p-value< 0.05). Of the eight included studies, four (50%) studies generalized about SSA with no country of interest; two (25%) studies were conducted in Nigeria; one (12.5%) reported about Uganda, Zambia, Guinea, Malawi Tanzania, Mali, Mozambique, Zimbabwe; and one (12.5%) reported about Ethiopia, Senegal, Zimbabwe and Uganda. These eight included studies reported evidence on more than one outcome of interest. Four studies reported about the prevalence of HPV-related cancers, seven studies reported about the incidence, four studies reported about mortality, and four studies reported about the trends of HPV-related cancers. Conclusion This study observation highlighted a gap of knowledge regarding the epidemiological data on the recent HPV prevalence in SSA, which will have a potential impact in determining the distribution of HPV on different body sites (cervix, penis, vagina, vulva, anus and oropharynx). Ongoing research projects are recommended in SSA to enhance the value of HPV, and HPV-associated cancers epidemiological data to inform strategies or/and policies on prevention, diagnosis, and treatment of HPV-related conditions.